From Social Exclusion to Impulsive Buying: FOMO’s Role in Digital Consumption Regret - Amdar Amdar; Elia Ardyan (Ilomata International Journal of Management, 2026)
Introduction: Shoppertainment platforms such as TikTok Shop and Shopee Live combine live interaction, social proof, scarcity cues, and instant checkout, creating a shopping setting that can heighten emotional arousal among Generation Z consumers. This study examines how social exclusion, fear of missing out, online impulsive buying, and post-purchase regret operate together in Indonesian shoppertainment. Methods: A quantitative cross-sectional survey was conducted among Indonesian Generation Z users of TikTok Shop and Shopee Live. Validated reflective measures were adapted from prior studies and translated through forward and back translation. The data were analysed using partial least squares structural equation modelling with bootstrapping. Results: The findings show that social exclusion is strongly associated with FOMO, but its direct association with online impulsive buying is not significant. FOMO is positively associated with online impulsive buying and post-purchase regret, while online impulsive buying is positively associated with post-purchase regret. Mediation testing indicates that FOMO fully mediates the relationship between social exclusion and online impulsive buying, and online impulsive buying partially mediates the relationship between FOMO and post-purchase regret. Conclusion: FOMO is the central psychological pathway through which social exclusion is translated into impulsive purchases in shoppertainment. The study highlights the ethical need for platforms and brands to reduce manipulative urgency cues and protect consumer agency.